Réflexion sur la prévision en relations internationales - Braillard, Philippe (Études internationales, 1980)
In the study of international relations, as indeed in all of the social sciences, reflections about the future are becoming increasingly numerous. They indicate frequently moreover a desire for systemization through recourse to rigourous techniques and procedures: the Delphi technique, the construction of scenarios, Systems analysis, operations research, decision matrices, graph theory, game theory, etc. This leads us to conclude often that the forecasting approach in international relations is undergoing a major quantitative and qualitative evolution.We seek to show however in this analysis that, contrary to appearances, forecasting research in international relations is characterized above all today by great epistemological weakness and by a remarkable incoherence, and that it is not therefore, for the most part, equal to its pretensions. We will attempt to determine why this is the case and if this situation is likely to change. In doing so, we will seek to identify both the possibilities and the limits of forecasting in this field.